Minimum Acceptable Diet and its Predictors among Children Aged 6-23 Months in Mareka District, Southern Ethiopia: Community Based Cross-Sectional Study - Feleke, Fentaw Wassie; Mulaw, Getahun Fentaw (International Journal of Child Health and Nutrition, 2020)
Background: Optimal infant and young child feeding practices are essential for normal growth, better health, and mental and physical development. Even though there are a lot of nutrition intervention programs in Ethiopia, still suboptimal feeding practices are prevalent. This study was devised to assess a level of minimum acceptable diet (MAD) and predictors among children aged 6-23 months in Mareka District, south Ethiopia. Method: A community-based cross-sectional study was employed on 662 study participants from August 15 to September 15/ 2015. They were selected by a multi-stage sampling technique. Data were collected by interviewer-administered semi-structured questionnaires. Statistical significance was declared at p-value <0.05 at multivariable logistic regression. Result: The study showed that 35.5 % of the children aged 6-23 months met the recommended MAD. Maternal primary and secondary education (AOR: 1.90; 95% CI: 1.15-3.16 and AOR: 2.06, 95% CI: 1.12-3.77), Media exposure (AOR: 2.16; 95% CI: 1.46-3.29), health facility delivery (AOR:2.52; 95% CI: 1.54-4.13), child age of 9-11 and 12-23 months (AOR:2.73; 95% CI: 1.41-5.49 and AOR:2.55; 95% CI: 1.39-4.69) and GMP service utilization (AOR: 4.09; 95% CI: 2.51-6.65) were associated with MAD of children. Conclusion: The level of MAD among children was low. Maternal educational status, media exposure, institutional delivery, child age, and GMP service utilization were associated with MAD. Increasing utilization of GMP service, health facility delivery, maternal education, and media promotion was recommended to increase the level of MAD.